Pengaruh Penambahan Gula Aren (Arenga pinnata Wurmb Merrill) Terhadap Cita-Rasa Wadi Ikan Patin (Pangasius sp.) - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2014)
“Wadi” is one of the traditional products which are highly preferred in Central Kalimantan and South Kalimantan. It is produced through a fermentation process for a minimum of 7 days, but the taste is still not obtained maximum. This study aims to determine the effect of adding palm sugar (Arenga pinnata Wurmb Merrill) to the taste of wadi from catfish in order to the adopted by people. The results showed that the best treatment in this study was the addition of palm sugar as much as 2.5%, and the nutritional values of wadi are follows: 27.86% of protein, 2.22% of fat, and 61.11% of water content. The mean value of organoleptic with criteria of like level given by seven trained panelists on appearance, aroma and taste is 7,71.